Evaluation of the Accuracy of Medical Terminology and Its Relationship to the Accuracy of Clinical Coding in Health Facilities: Systematic Literature Review - Firdayana Firdayana; Mieke Nurmalasari; Hosizah Hosizah; Sandra Hakiem Afrizal (Jurnal Ners, 2023)
Clinical Coding will be accurate if the proper medical language is used while writing. Clinical coding that is appropriate may help healthcare organizations with things like accurate care, billing for services, strategic planning, and statistical and financial analysis. The purpose of the study, which employed a methodical literature analysis, was to ascertain the link between the clinical coding accuracy in healthcare institutions and the correctness of medical terminology. This study is an organized review of the literature. Google Scholar, Garuda, Neliti, the Indonesian Scientific Journal Database (ISJD), Semantic Scholar, PubMed, and ScienceDirect are the databases that were used. PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis) is the strategy used for the literature selection. The Reinforcement of Observational investigation Reporting in Epidemiology (STROBE) tool was used to evaluate the caliber of the literature in this investigation. The study's findings show that the average value of clinical coding accuracy in healthcare facilities is 48%, with 14 articles having accuracy levels above or below 50%. The average value of medical terminology accuracy in healthcare facilities is 55%, with 11 articles having accuracy levels below 50. Up to 79% of the study's findings indicated a connection between the precision of clinical coding and the precision of medical language. Comparatively, 21% of respondents claimed there was no connection between clinical coding accuracy and medical terminology correctness.